Surgical management of intrathoracic goitres (2019)
ABSTRACT: Background Intrathoracic goitres (ITG) often present with compressive symptoms and require specialised care by experienced surgical teams. Most ITG can be accessed by a transcervical approach (TCA) and only between 1 and 15% will require an extracervical approach (ECA). Many controversies exist regarding the clinical presentation, evaluation, selection of cases for ECA, surgical technique and outcomes. This paper reviews the recent literature on the management, outcomes and evidence-based treatment strategies of ITG. Methods We conducted a review of the literature on the evaluation, management and outcomes of surgery for ITGs. Results The incidence of cancer in the ITGs ranges between 4 and 20%. Multiplanar CT scanning offers the best preoperative evaluation and aids to determine the approach. Most ITG can be accessed by TCA and ECA are only needed in maximum 15% of cases. In experienced hands, the outcome of these surgeries is comparable to thyroid surgery for non-ITG. Conclusions Surgery for ITG is challenging. The experienced surgeon however, with few exceptions can address ITG via TCA, with outcomes comparable to those of uncomplicated thyroid surgery.